Interpersonal Trust and Suicide Ideation Among Adolescent Psychiatric Inpatients: An Indirect Effect via Perceived Burdensomeness. Issue 1 (25th January 2018) - Hill, Ryan M.; Penner, Francesca; Vanwoerden, Salome; Mellick, William; Kazimi, Iram; Sharp, Carla
Abstract : The identification of theoretically and empirically supported correlates of suicide ideation is important to improve treatment approaches to suicide. This study sought to examine the association between interpersonal trust (theoretically conceptualized as a distal risk marker) and suicide ideation in adolescence. Specifically, it was hypothesized that interpersonal trust would be negatively associated with suicide ideation via perceived burdensomeness and thwarted belongingness (conceptualized as more proximal risk markers). Data were drawn from a cross‐sectional sample of 387 adolescent inpatients between the ages of 12 and 17 years ( M = 14.72, SD = 1.49). The sample was 63.6% female, 37.5% Hispanic, 26.9% African American/Black, and 25.8% Caucasian. Adolescents completed a series of self‐report measures to assess thwarted belongingness, perceived burdensomeness, interpersonal trust, depressive symptoms, and suicide ideation. A structural equation model was fit to the data, and results demonstrated a significant indirect path from interpersonal trust to suicide ideation via perceived burdensomeness, but not thwarted belongingness. Results suggest that interpersonal trust may be a distal risk marker for suicide ideation and that interventions to increase interpersonal trust may help prevent the development of thwarted belongingness, perceived burdensomeness, and suicide ideation.